Validasi Metode Penetapan Kadar Etanol pada Parfum Isi Ulang yang Dijual di Kota Madiun menggunakan Metode Kromatografi Gas Detektor FID (Flame Ionization Detection) - Wigyaningrum, Amelia Ike; Kurniawati, Nurrizka; Erikania, Susanti (Indonesian Journal of Medical and Pharmaceutical Science, 2024)
Background: Perfume and fragrance oils are among the thousands of industrial products that are in demand by the public. The general public uses fragrance oils as body fresheners, for clothing and for rooms. Perfume is a mixture of essential oils and aromatic compounds, binders and solvents used to provide fragrance to the human body, objects or rooms. The purpose of this study was to analyze the ethanol content in refill perfume products. Method: This study used gas chromatography, gas chromatography is a dynamic method for the separation and detection of volatile compounds in a mixture. Gas chromatography can be used to determine the concentration of ethanol. This method has been improved and shows a significant increase in determining the concentration of ethanol. The tests carried out include qualitative and quantitative tests. Results: The results of the qualitative test showed that all perfume samples were positive for ethanol. While the results of the quantitative test to determine the ethanol content in perfume samples showed results of 1.9%; 2.04%; 2.03%; 1.83% and 1.84%. According to BPOM, the safe ethanol content in perfume is 5% calculated as % of ethanol and isopropanol. Conclusion: The FID detector gas chromatography method is efficiently used in determining the ethanol content in perfume. The results of the calculation of the content values contained in sequence from samples 1,2,3,4, and 5 are 1.9%; 1.49%; 2.03%; 1.83% and 1.84%. All refill perfume samples sold in perfume shops in Madiun City meet BPOM standards.